THE LATE PALEOCENE ECOLOGIC CRISIS IN EPICONTINENTAL BASINS OF THE EASTERN PERITETHYS: MICROBIOTA AND ACCUMULATION CONDITIONS OF SAPROPELIC BED - Stupin S.I.; Muzylev N.G. (My University, 2001)
In the Upper Paleocene sedimentary sequence of the Eastern Peritethys, there is a bed highly enriched in organic matter (sapropel). Investigation of microbiota, mainly of foraminifers, showed that the bed accumulated in response to paleoecologic crisis related to substantial oxygen deficiency in the paleobasin, which led to a significant extinction of benthic fauna. The true anoxic environments and related contamination by hydrogen sulfide have not been realized however. A vast transgression in the Eastern Peritethys appears to be the likely reason for the sediment enrichment in organic matter. This event caused submergence of a swampy coastal plain, subsequent active inflow of biophile elements, and abundance outburst of organic-walled phytoplankton and cyanobacteria.
Keywords: Paleocene; Peritethys; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен